2020
DOI: 10.7717/peerj.9448
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of the complete chloroplast genomes of three Chrysanthemum boreale strains

Abstract: Background Chrysanthemum boreale Makino (Anthemideae, Asteraceae) is a plant of economic, ornamental and medicinal importance. We characterized and compared the chloroplast genomes of three C. boreale strains. These were collected from different geographic regions of Korea and varied in floral morphology. Methods The chloroplast genomes were obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 63 publications
2
7
0
Order By: Relevance
“…The nucleotide diversity was higher in the LSC and SSC compared to SSC regions and identified the following hypervariable regions across the Calanthe group plastome: trnS-GCU -trnG-GCC , rpoB-trnC-GCA , trnE-UCC -trnT-GGU , rpl32-trnL-UAG , ccsA-ndhD and protein-coding genes psbL, clpP and rpl32. The markedly high divergence observed in these genes and intergenic regions is similar to that observed in other angiosperms [4,64,65] and may be attributed to rapid genome evolution due to higher mutation rates compared to other regions [66].…”
Section: Comparative Analysissupporting
confidence: 76%
“…The nucleotide diversity was higher in the LSC and SSC compared to SSC regions and identified the following hypervariable regions across the Calanthe group plastome: trnS-GCU -trnG-GCC , rpoB-trnC-GCA , trnE-UCC -trnT-GGU , rpl32-trnL-UAG , ccsA-ndhD and protein-coding genes psbL, clpP and rpl32. The markedly high divergence observed in these genes and intergenic regions is similar to that observed in other angiosperms [4,64,65] and may be attributed to rapid genome evolution due to higher mutation rates compared to other regions [66].…”
Section: Comparative Analysissupporting
confidence: 76%
“…The DNA sequences of seven low-copy nuclear genes and nrITS were combined to reconstruct a time-calibrated phylogeny of subtribe Artemisiinae ( Figure 2 ). In the monophyletic Chrysanthemum group, Chrysanthemum and Ajania were well resolved, agreeing with capitulum morphology and suggesting the low resolving power of cp and ITS markers ( Zhao et al, 2010 ; Hong et al, 2015 ; Tyagi et al, 2020 ; Masuda et al, 2022 ). Within Chrysanthemum , the C. indicum complex and C. zawadskii complex diverged, which temporally coincide with the late Cenozoic uplift of Northern QTP and associated climatic heterogeneity between eastern and central Asia.…”
Section: Biodiversity and Phylogenetic Relationshipmentioning
confidence: 60%
“…The cp genome with maternal genetic characteristics has the advantages of multi-copy and conservative structure. The combination of cp genome and high-throughput sequencing technology has become an effective means of plant genetic resources research, which facilitates the study of Chrysanthemum classification and genetic resources ( Tyagi et al, 2020 ; Masuda et al, 2022 ). The accumulation of whole genome sequencing data of Chrysanthemum ( Song et al, 2018 ; Nakano et al, 2021 ; van Lieshout et al, 2022 ) and relevant taxonomic groups will enable the comprehensive phylogenomic analyses to reveal the hybridization/polyploidization events leading to the speciation and formation of CM.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…Divergent hotspots play a significant role in species identification and phylogenetic information. Moreover, IR regions often show lower sequence divergence than SSC and LSC regions [67], this probably due to higher mutation rates lead to rapid genome evolution compared to other regions [68]. In our study, this phenomenon was evident that the SSC area showed the maximum nucleotide diversity followed by the LSC region, and the IR regions had the lowest Pi value (Fig.…”
Section: Comparison Of Ferula Plastid Genomementioning
confidence: 49%